50 Battles that Changed the World - Weir, William, 1928- (Rawalpindi, Pakistan Army Publishing House, 2012)
This book selects 50 battles throughout history that are discussed in some detail. Rather than celebrating warfare, this book takes a brief look at the 50 battles that have had the most profound impact on world history. Listed in order of importance for our world today, they range from the ancient world to the present and span the globe. The author has selected the battle and provides his reasoning for why they were selected as those with most impact on World History.
Include Colour Illustration, Glossary, Bibliography and Index
Keywords: Military history -- Naval history -- Battles